Criptomoedas complementares: uma tipologia para moedas locais, sociais e comunitárias criadas em blockchain - Daneluzzi, Fábio Lemes (2018)
Blockchain-based cryptocurrencies are a new group of digital currency. By allowing a highly decentralization, without the need of a central issuer to control the digital system, those new currencies have been created with increasing speed since 2009 after the emergence of Bitcoin, the first digital currency based on such technology. In this context, a particular group of cryptocurrencies have arisen, called 'Complementary Cryptocurrencies' in this research. These cryptocurrencies seek to meet specific demands of society, such as financial inclusion, social development or environmental preservation, in some cases at specific communities, as well as do the 'traditional' complementary and community currencies. Since this phenomenon is quite new, there are few studies that aim to understand it. This, therefore, is the goal of this research. Through a study of 28 different complementary cryptocurrencies and based on 8 different classification models designed to complementary and community currency already present in the literature, this research allowed the proposal of a new, specific typology for such a universe. Composed by 4 dimensions, this typology allowed to segregate the complementary cryptocurrenciesin 10 different groups, allowing greater clarity about their similarities and differences in strategic and technical aspects. It is expected that this research helps professionals, institutions and researchers involved or interested in themes such as solidarity finance, complementary currencies and cryptocurrency, to understand this new phenomenon and its particularities, not only through the mapping of complementary cryptocurrency done, but also through the typology created, using it as a model to better group, distinguish and compare projects of this nature.